Some Identity Expression Ways of Senior Pupils’ - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2003)
The article deals with the problem of identity of the senior school age pupils. In the context of habits of emotional experiences of senior students at schools and gymnasiums, some of the identity development traits are revealed. With that purpose in mind, the origins of senior pupils’ positive and negative emotional experiences and their interrelationship with their identity are revealed. Also, major ways of expressing their emotions are discussed. The conclusion is made that positive emotions more frequently are evoked by the satisfaction of the social needs, negative – by higher personal needs. Positive emotions reflect more social and interpersonal identity development negative – personal, closely related to professional and interpersonal development. On the other hand, though the identity development ought to take place both in national and natural spheres, emotions of senior pupils are rarely related to them and they barely contribute to pupils’ identity development process. On the other hand, emotional development courses of senior school age students most often reflect practical, communicational and romantic emotional experiences. Originating from communication, work and acquaintance with new environments. These types of emotions also influence formation of their identity.